Determination of 11 ginsenosides in ginseng health wine by HPLC - HU Yang, LI Xianzhi, MAO Qiongli, LIU Yang, YAN Ling, ZHU Yan, SHI Hao (Zhongguo niangzao)
In this study, a high performance liquid chromatography (HPLC) method was established for the simultaneous determination of 11 ginsenosides (ginsenoside Rg1, Re, Rf, Ra2, Rb1, Rc, Ra1, Ro, Rb2, Rb3, Rd) in ginseng health wine. Using Agilent SB C18 column (4.6 mm×250 mm, 5 μm), with acetonitrile-0.1% phosphoric acid as mobile phase gradient elution, flow rate 1.0 ml/min, column temperature 28 ℃, the detection wavelength of ginsenoside was 203 nm, and the injection volume was 10 μl. The results showed that 11 ginsenosides all had good linear relationship in their respective concentration range (R2≥0.999 9). The limits of detection were 1.52-3.03 mg/L, and the limits of quantitation were 4.59-9.18 mg/L. The relative standard deviation (RSD) of precision test, stability test and repetition test was less than 5%. The average recovery rate was 95.39%-101.96%, RSD was 0.07%-2.46%. The method had the advantages of simple operation, high accuracy and good repeatability, and could be used for the determination of 11 ginsenosides in ginseng health wine.